The Materials of Nikolai Okunev’s Expedition of 1917 on the Wall Paintings of Parkhali - Zakharova, Anna V.; Maltseva, Svetlana V. (Actual Problems of Theory and History of Art, 2017)
The paper presents a reconstruction of the iconographic program of the 10th century. Georgian murals in the church of St. John the Baptist in Parkhali (Tao-Klardjeti, nowadays Eastern Turkey). The wall paintings have been white-washed for many decades. Before that, in summer of 1917, they were examined and photographed by the expedition headed by Nikolai Okunev (1885–1949). The photographs are now kept in the archive of the Institute of History of Material Culture in St. Petersburg, they are here published for the first time.The partially damaged wall paintings were mainly preserved in the apse. There was an image of Christ in Majesty in the conch. Then followed a row of apostles with the Virgin probably flanked by archangels in the middle, and another row of prophets. In the next two tiers there were some Gospel scenes. The authors identified Annunciation, Meeting of the Virgin with St. Elizabeth, Nativity, Presentation in the Temple, Baptism, Transfiguration,and the Raising of Lazarus, as well as some scenes from the Passion cycle: the Last Supper, Crucifixion,Deposition from the Cross. The images of the lowest tier so far remain unidentified. In the altar window there was a half-figure in a medallion representing the Holy Zion. It was flanked by two compositions, probably Moses receiving the Law and Melchisedec before the altar. It has been suggested by other scholars that the wall paintings in Parkhali were similar to those in a neighboring Otkhta Eklesia dating to the same period. The authors make more detailed comparisons between these two ensembles and discuss them in a wider historical and artistic context.
Keywords: mediaeval Georgian wall paintings; Parkhali; Otkhta Eklesia; Tao-Klardjeti; Nikolai Okunev; Institute of History of Material Culture